The Middle Pleistocene small mammals from the lower layers of Tunel Wielki Cave (Kraków-Częstochowa Upland): An Early Toringian assemblage in Poland. (10th March 2021) - Berto, Claudio; Nadachowski, Adam; Pereswiet-Soltan, Andrea; Lemanik, Anna; Kot, Małgorzata
Abstract: Among the well-known small mammal assemblages of the Kraków-Częstochowa Upland, the one from Tunel Wielki Cave is one of the most interesting for the Pleistocene biochronology of Poland. As a new trench was opened in 2018, it was possible to reanalyse the entire sequence. Its complex stratigraphy is divided into two phases: the Holocene–Late Pleistocene series and the Middle Pleistocene. In this work, we present the study of a small mammal assemblage coming from this site, with a focus on the Middle Pleistocene material. The total assemblage was composed of 268 individuals divided into 43 taxa. In the Middle Pleistocene series, two oscillations, one mild and one cold, were detected. Among the determined taxa, some are crucial for defining the chronology of the lower part of the sequence. Arvicola mosbachensis was recorded, consisting of the first finding of this species in Poland. The presence of Pliomys coronensis was confirmed, as well as that of Pliomys episcopalis . The occurrence of Microtus cf. arvalis, Microtus cf. agrestis among rodents, Myotis bechsteinii cf. robustus, and Plecotus cf. abeli among bats, as well as the analyses of the morphological characters of the other species confirm that this part of the sequence can be related to the Middle Pleistocene, precisely to a moment between Marine Isotope Stages (MISs) 14 and 11, establishing Tunel Wielki Cave as the first Early Toringian site in Poland.